POTENTIAL ANTIOXIDANT ACTIVITY OF METHANOL EXTRACT OF SINGKIL LEAF (Premna cordifolia Roxb.) USE DPPH METHOD: A MINI RIVIEW - Firmansyah, Muchammad Ravi; Daniel, Daniel; Marliana, Eva (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Singkil leaves (Premna cordifolia Roxb.) are a plant that is widely found in Kalimantan, and usually grows in the yard of houses or plantations. The antioxidant activity test of methanol extract from Singkil leaves (Premna cordifolia Roxb.) has been done. This research aims to determine the antioxidant properties of methanol extract from leaves. Based on the results of the phytochemical test, it is known that the methanol extract contains alkaloids, flavonoids, phenolics, steroids and triterpenoids. The results of the literature show that the methanol extract exhibits antioxidant activity in the